Christian moderns freedom and fetish in the mission encounter - Keane, Webb 1955- (Berkeley, CA University of California, 2007)
Includes bibliographical references and index.
Keywords: Missions -- Indonesia -- History; Missions, Dutch -- history; Calvinism -- comparative studies; Religion and culture; Conversion -- Christianity; Netherlands -- religion; Indonesia -- religion